A comparative cytogenetic study of five piranha species (Serrasalmus, serrasalminae) from the Amazon basin - Nakayama, Celeste Mutuko; Porto, Jorge Ivan Rebelo; Feldberg, Eliana (Genetica, 2002)
Cytogenetic studies were conducted on five piranha species belonging to the genus Serrasalmus, subfamily Serrasalminae (Serrasalmus altispinis, S. compressus, S. elongatus, S. manuelli, and S. spilopleura). All the species were collected in the Amazon basin: confluence of Negro and Solimões Rivers (CatalãoLake), Solimões River (Marchantaria Island - Camaleão Lake), Uatumã River (Hydroelectric Power Station of Balbina), and Pitinga River (Hydroelectric Power Station of Pitinga). All the five species possess 2n = 60 chromosomes with 5-12 subteloand acrocentric chromosomes bearing nucleolar organizer regions. A proximal C-band positive heterochromatin block was evident on the long arms of a medium-sized metacentric chromosome pair in all the analized species, thus making it a cytogenetic marker for the genus. It is hypothesized that 2n = 60 chromosomes represents a derived feature in terms of the chromosomal evolution of piranhas because the basal lineages possess 2n = 62. Both Robertsonian centric fusion and non-Robertsonian rearragements such as pericentric inversions seem implicated in the chromosomal evolution of this group.
Keywords: Animals; Chromosome Analysis; Chromosome Banding Pattern; Classification; Evolution; Female; Fish; Genetics; Karyotyping; Male; Animal; Chromosome Banding; Cytogenetic Analysis; Evolution; Female; Fishes; Karyotyping; Male; Animalsia; Characiformes; Robertsonia; Serrasalminae; Serrasalmus; Serrasalmus Compressus; Serrasalmus Spilopleura